Prenatal Study of Testes Growth and Histological Development 1- Fetal Sheep.: Amin F.A.S. M and ALwan A.F. - S. M, Amin F.A. (The Iraqi Journal of Veterinary Medicine, 2010)
This study was conducted on 200 samples of females Karadi sheep genitalia contains 207 fetuses . These samples were collected from slaughter house in Sulaimani reigion during the period from June 2007 to the end of May 2008. Sheep genitalia consisted of 193(96.5%) single and 7(3.5%) twin fetuses, amonge them 122 (58.92%)and 84(41.06) were in the right and left horns ,respectively. The genitalia that contain fetuses with clear external sex organs was 141, of these 74 male and 67 female fetuses different Crown Rump Length (CRL), while 66 fetus their sex could diagnosis after abdominal opened. The results showed the weight of the fetal body and testes as well as the length of scrotum were increased with an increasing of the fetal CRL. The appearance of the fetal testes in the inguinal ring was when CRL=22cm .80 day; in the scrotum 32 cm. 100 day ; Histological sections of the fetal testes were showed the density of fibroblast layer and connective tissue capsules as well as the appearance of seminiferous tubules containing a few spermatogonia cells and small sertoli and leydig cells at early CRL=10 cm 55 day; , with increasing fetal CRL the seminiferous tubules filled with different types of spermatogonia and spermatocytes cells as well as increasing in the number of sertoli and leydig cells were recorded at CRL= 20.3 cm. 75 days; While the metamorphosis spermatid were seen at CRL=24cm . 80-85 day; Conclusions : Fetal sheep seminiferous tubules early in gestation contain different types of spermatognium and spermatocyte cells appear in the testes after 50 days, and metamorphosis spermatid were seen after 80 days of intra uterine life no sperm was seen in fetuse testes.. It was concluded that the fetal testes in early gestation could be secreted testosterone which lead to increases in fetal testes development and growth of the germinal and somatic cells